Erectile Dysfunction: Just a Difficulty of the Sex Organs? - Teresa Rodríguez Rodríguez (Revista Finlay)
Difficulties in sexual response have always been a cause of concern and suffering for people who suffer them, and their partners. One of the alterations of this condition in the man and that more attention demands is the erectile dysfunction, precisely for compromising in a significant way the sexual performance, the personal satisfaction, the commitment with the partner and their self-esteem. The health personnel who care for these patients must be updated about their causes, current treatments, new approaches that deepen its etiology, evolution, implications and association with other diseases. Therefore, improving the prevention, treatment and rehabilitation of alterations in sexual response and especially erectile dysfunction is a goal to be achieved, which presupposes knowledge and awareness of all professionals and health decision makers.